Sex differences in youth elite swimming - Senefeld, J. W.; Clayburn, A. J.; Baker, S. E.; Carter, R. E.; Johnson, P. W.; Joyner, M. J. (PLOS ONE, 2019)
Background The timing and magnitude of sex differences in athletic performance during early human development, prior to adulthood, is unknown. Objective To compare swimming velocity of boys and girls for all Olympic-length freestyle swimming events to determine the age of divergence in swimming performance. Methods We collected the all-time top 100 U.S. freestyle swimming performance times of boys and girls age 5 to 18 years for the 50m to 1500m events. Results Swimming performance improved with increasing age for boys and girls (p<0.001) until reaching a plateau, which initiated at a younger age for girls (15 years) than boys (17 years; sex×age; p<0.001). Prior to age 10, the top 5 swimming records for girls were 3% faster than the top boys (p<0.001). For the 10th-50th places, however, there were no sex-related differences in swimming performance prior to age 10 (p = 0.227). For both the top 5 and 10th-50th places, the sex difference in performance increased from age 10 (top 5, 2.5%; 10th-50th places, 1.0%) until age 17 (top 5, 7.6%; 10th-50th places, 8.0%). For all places, the sex difference in performance at age 18 was larger for sprint events (9.6%; 50-200m) than endurance events (7.1%; 400-1500m; p<0.001). Additionally, the sex-related difference in performance increased across age and US ranking from 2.4% for 1st place to 4.3% for 100th place (p<0.001), indicating less depth of performance in girls than boys. However, annual participation was ~20% higher in girls than boys for all ages (p<0.001). Conclusion The top 5 girls demonstrated faster swimming velocities and the 10th-50th place girls demonstrated similar swimming velocities than boys (until ~10 years). After age 10, however, boys demonstrated increasingly faster swimming velocities than girls until 17 years. Collectively, these data suggest girls are faster, or at least not slower, than boys prior to the performance-enhancing effects of puberty.